Effects of Topical Fucosyl-Lactose, a Milk Oligosaccharide, on Dry Eye Model: An Example of Nutraceutical Candidate - Bucolo, Claudio; Musumeci, Maria; Salomone, Salvatore; Romano, Giovanni Luca; Leggio, Gian Marco; Gagliano, Caterina; Reibaldi, Michele; Avitabile, Teresio; Uva, Maurizio G.; Musumeci, Salvatore; Drago, Filippo (Frontiers in Pharmacology, 2015)
Purpose: Colostrum has been proposed to treat severe dryness and problematic eye lesions showing a beneficial effect. The aim of the study was to investigate the effect of 2-fucosyl-lactose, a natural sugar present in the human colostrum, in an experimental dry eye. Methods: Dry eye was induced in adult male New Zealand albino rabbits by topical administration of 1% atropine. Tear volume (Schirmer’s test), tear film breakup time (TBUT), corneal staining and tear osmolarity were assessed. Fucosyl-lactose eye drops was instilled at different concentrations (0.01%, 0.1%, 1%). Results: After 24 hours from first atropine administration, tear volume and TBUT values were significantly improved in groups treated with 2-flucosyl-lactose in a dose-dependent manner. Tear volume increased from 5.25 to 10.75 mm and TBUT values from 8.75 to 34.5 seconds with 0.01% or 1% 2-flucosyl-lactose treatment, respectively. No changes were observed in terms of corneal staining among the all groups treated with 2-fucosyl-lactose. Atropine instillation caused an increase of tear osmolarity (428 mOsm/L), which was reversed by topical treatment with 2-fucosyl-lactose at all doses. Conclusions: The present study demonstrated that 2-fucosyl-lactose, a human milk oligosaccharide, has protective effect on tear film stability.